Health Benefits of Antioxidant Bioactive Compounds in the Fruits and Leaves of Lonicera caerulea L. and Aronia melanocarpa (Michx.) Elliot - Bogdan-Stefan Ne; Ovidiu Cristian Oprea; Ticuta Negreanu-Pirjol; Florentina Nicoleta Roncea; Ana-Maria Prelipcean; Oana Craciunescu; Andreea Iosageanu; Victoria Artem; Aurora Ranca; Ludmila Motelica; Anca-Cristina Lepadatu; Madalina Cosma; et al. (MDPI AG, 2023)
Lonicera caerulaea L. and Aronia melanocarpa (Michx.) Elliot fruits are frequently used for their health benefits as they are rich in bioactive compounds. They are recognized as a source of natural and valuable phytonutrients, which makes them a superfood. L. caerulea presents antioxidant activity three to five times higher than other berries which are more commonly consumed, such as blackberries or strawberries. In addition, their ascorbic acid level is the highest among fruits. The species A. melanocarpa is considered one of the richest known sources of antioxidants, surpassing currants, cranberries, blueberries, elderberries, and gooseberries, and contains one of the highest amounts of sorbitol. The non-edible leaves of genus Aronia became more extensively analyzed as a byproduct or waste material due to their high polyphenol, flavonoid, and phenolic acid content, along with a small amount of anthocyanins, which are used as ingredients in nutraceuticals, herbal teas, bio-cosmetics, cosmeceuticals, food and by the pharmaceutical industry. These plants are a rich source of vitamins, tocopherols, folic acid, and carotenoids. However, they remain outside of mainstream fruit consumption, being well known only to a small audience. This review aims to shed light on L. caerulaea and A. melanocarpa and their bioactive compounds as healthy superfoods with antioxidant, anti-inflammatory, antitumor, antimicrobial, and anti-diabetic effects, and hepato-, cardio-, and neuro-protective potential. In this view, we hope to promote their cultivation and processing, increase their commercial availability, and also highlight the ability of these species to be used as potential nutraceutical sources, helpful for human health.